Analisis Pengaruh Dana Pihak Ketiga Dan Tingkat Suku Bunga Kredit Terhadap Profitabilitas Bank BUMN - Tofan, Muhamad; Munawar, Aang; Supriadi, Yoyon; Effendy, Marwan (LPPM Institut Bisnis dan Informatika Kesatuan, 2022)
This study aims to see the effect of third parties and credit interest rates on profitability at state-owned banks. The analytical method used in this research is multiple linear regression with ROA profitability being the dependent variable and two independent variables, namely Third Party Funds and Credit Interest Rates. The results of data processing have obtained a regression model = Y: 0.934 + 2.369X1 + -0.089X2. The regression coefficient shows that if each increase in third party funds is 2.369 one unit, it is predicted that it will increase profitability by 0.934 units and vice versa. The coefficient of determination (R1) is 0.299, this shows that the variable Third Party Funds and the Credit Interest Rate contribute or influence 29% on the profitability variable ROA at BUMN Banks. Partially, the test results show that each variable of third party funds has a positive and significant effect on ROA so that it is accepted and credit interest rates have a negative and insignificant effect on ROA. Simultaneously, the results of the F test show that together the variables of Third Party Funds and Interest Rates have a significant effect on ROA so that they are accepted. Keywords: Third Party Funds, Profitability Ratios, ROA, Credit Interest Rates